Australia's future submarine: shaping early adaptive designs through test and evaluation. Issue 1 (1st January 2016) - Joiner, Keith F.; Reay Atkinson, Simon
Abstract: The Australian Government selected France's Direction des Constructions Navales Services to design Australia's future submarine, the Shortfin Barracuda. This paper evaluates different system developmental approaches that can be applied, such as the U.S. acquisition life cycle and a research, engineer, design, adapt, reflect (RADER) model. The evaluation showed a need for deliberate regard for the significant philosophical, political, military, cultural and economic differences of the French practices compared to U.S., U.K. and Australian. The paper reviews major lessons learned in Australian acquisitions regarding early preview test and evaluation (T&E), including the Collins Class Submarine, and proposes 11 T&E goals, especially early commitment to an estimated seven test sites needed to ensure the early design is proven and low risk. To save substantial overall time and rework, greater investment is needed in the social spaces for critical thinking and T&E to guide the submarine towards a continuously evolving design and build.